Struktur dan Stratifkasi Sosial Umat Khonghucu di Kabupaten Tuban Jawa Timur - Joko Tri Haryanto (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
People of Confucianism as subunsur in the wider community also havea social structure and social stratifcation that support the developmentand sustainability of Confucius’s own people. Research on the structureand social stratifcation is taking Confucian people in Tuban district of EastJava as target people with the method of observation and interviews witha qualitative approach. Confucian social structure people in Tuban in EastJava were not only distinguished in spiritual groups and groups of people,but there are other structures of the pagoda board even have a social rolein a very large religious community Confucian Tionghoa in Tuban in EastJava.Keywords: Social structure, social stratifcation, Tionghoa, Confucian,Tuban in East Java